"Adolescent metabolic phenotypes and early adult metabolic syndrome: Tehran lipid and glucose study". Issue 2 (August 2015) - Hosseinpanah, Farhad; Salehpour, Mostafa; Asghari, Golaleh; Barzin, Maryam; Mirmiran, Parvin; Hatami, Hossein; Azizi, Fereidoun
Highlights The most frequent phenotype among adolescents was high TGs and low HDL-C. Adolescent metabolic phenotypes predict adult MetS independent of BMI change. The discriminative power of adolescent metabolic phenotypes was weak. The phenotypes add more controversy on their clinical utility in adolescence.